Pedagogical Practice - Approach from the Perspective of Online Learning - Popa, Doinița (Didactica Danubiensis, 2024)
The hybrid approach to pedagogical practice has become increasingly necessary in the context of technology development and recent educational changes. Hybrid pedagogy, which combines traditional face-to-face learning with elements of online education, offers a comprehensive range of advantages that meet the needs of both teachers and students, ensuring they are well-informed and knowledgeable about its benefits. This gives teachers and students greater flexibility and accessibility, enabling better adaptation to various educational needs.